EUROPEAN VALUES AND VALUE ORIENTATIONS OF UKRAINIAN SOCIETY: THE RELATIONSHIP PROBLEMS - Мадрига, Т. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article deals with the problem of value orientations of Ukrainian society and their relationship with European values. Submitted system of values that serve as the principles of civil and political institutions of modern European countries and the European Union. Analyzed changes in the value paradigm of modern Ukrainian society.